The Effect Of Leverage And External Audit Quality On Tax Avoidance In Food And Beverage Companies - Nadila, Siti Qoriatul; Aulia, Yoosita (Dhana, 2025)
This study aims to determine the effect of leverage and external audit quality on tax avoidance in food and beverage subsector companies listed on the IDX in 2020-2023. This research is a quantitative study using secondary data in the form of company financial reports obtained from the Indonesia Stock Exchange website. The research population amounted to 25 companies. Determination of the sample using purposive sampling method and obtained a sample of 18 companies in 4 years of observation so that the total sample obtained was 72 companies. The data analysis technique used in this research is logistic regression analysis and processed using SPSS version 25. The results obtained based on the wald test show that leverage has an effect on tax avoidance, external audit quality has no effect on tax avoidance, and leverage and external audit quality simultaneously have no effect on tax avoidance.